Bacterial enteric pathogens and serum interleukin-6 levels in children with acute diarrhea - Herlina Herlina; Jeanette Irene Manoppo; Adrian Umboh (Paediatrica Indonesiana, 2016)
Background Acute diarrhea is currently one of the major causes of morbidity and mortality in developing countries. A wide range of enteric pathogens, including bacteria, is responsible for the pathogenesis of acute infectious diarrhea. Recent studies have shown an increase in acute phase proteins, such as serum interleukin-6 (IL-6) levels, in patients with acute bacterial gastroenteritis. Thus, IL-6 may be a useful marker to differentiate bacterial from non-bacterial enteric pathogens.Objective To assess for a correlation between bacterial enteric pathogens and serum IL-6 levels in children with acute diarrhea.Methods We conducted a cross-sectional study from November 2013 to March 2014 in two hospitals in Manado. Subjects were children aged 1-5 years with acute diarrhea and good nutritional status. Subjects’ provided stool samples for bacterial culture and microscopic examination, as well as blood specimens for serum IL-6 measurements. Data was analyzed by linear regression and Pearson’s correlation tests for a correlation between bacterial enteric pathogens and serum IL-6 levels.Results In children with acute diarrhea, those with bacterial enteric pathogens had significantly higher mean serum IL-6 than those with non-bacterial enteric pathogens (r = 0.938; P < 0.001).Conclusion Serum IL-6 levels are significantly more elevated in children with acute diarrhea and bacterial enteric pathogens. Therefore, serum IL-6 may be a useful marker for early identification of bacterial gastroenteritis in children aged 1-5 years. [Paediatr Indones. 2016;56:144-8.].